Genetic counseling and the role of genetic counselors in the United States - Schaaf, Christian P. (Medizinische Genetik, 2021)
Genetic counselors represent an indispensable, well-established, and well-integrated group of healthcare providers in the field of genetic and genomic medicine in the United States. They work with other members of the healthcare team to provide information and support to individuals and families concerned with genetic disorders. With more than 5,000 certified genetic counselors in the U.S. and an expected growth of 100 % over the next decade, genetic counseling represents one of the fastest-growing professions in the U.S. Genetic counselors work in clinical environments (e. g., hospitals), in companies (e. g., genetic testing firms), and as consultants to medical practices and others. Twenty-six states license genetic counselors as practitioners who can bill independently, with licensure applications underway in the remaining 24 states. Physicians, genetic counselors, and diagnosticians represent the three pillars of comprehensive, integrated genomic medical care. Within this triad, genetic counselors see their primary role in procuring and interpreting family and medical histories, assessing inheritance, quantifying chances of recurrence, facilitating decision-making regarding genetic testing options, and explaining the results of such testing to the respective individuals within the greater context of their families.